ОЦЕНКА ЗНАНИЙ СТУДЕНТОВ В ВЫСШИХ УЧЕБНЫХ ЗАВЕДЕНИЯХ И АНАЛИЗ ИХ ЭФФЕКТИВНОСТИ - Базарбаева, А.К. (SCIENCE and SOCIETY, 2025)
This article examines the importance of evaluation criteria for students in higher education institutions and their contribution to improving the quality of education. The objectives and tasks of the evaluation process are analyzed, and an example of a standard evaluation system is provided. Various evaluation systems, their characteristics, and an analysis of their strengths and weaknesses are discussed. The article compares norm-referenced and criterion-referenced evaluation approaches, using leading European universities as examples.